Estructura horizontal y diversidad de especies forestales en el bosque de terraza baja, distrito de Mazán, Loreto. 2024 - Ahuite Shupingahua, Juan Gualberto (2025)
In a study on horizontal structure and forest species diversity in the low terrace forest in cutting plot 20 (PC 20) within the management unit of forest concession N° 16 MAY/C-D-003-14, Mazán district, Loreto, a total of 69 species, 63 genera, 25 families and 364 individuals were recorded in plot 1. In plot 2, 73 species, 66 genera, 26 families and 389 individuals were identified. Iryanthera elliptica stood out as the most significant species, with an Importance Value Index (IVI) of 22.81 % in plot 1 and 24.61 % in plot 2, followed by Pouteria ephedrantha, with values of 18.41 % and 18.29 %, respectively. The Margalef index showed values of 11.64 in plot 1 and 12.07 in plot 2, showing a moderately high diversity in both areas. Simpson's index (D) for all species was 0.03813 in plot 1 and 0.03774 in plot 2, also reflecting high diversity. The highest contributions to this index were from Iryanthera elliptica (0.00822 in plot 1 and 0.00905 in plot 2) and Pouteria ephedrantha (0.00773 and 0.00764, respectively). The Shannon-Wiener diversity index (H′) recorded 3.68 in plot 1 and 3.72 in plot 2, reaffirming a medium to high diversity. These species stood out for their relative abundance, consolidating their ecological relevance in both plots. The results confirm differences in structure and diversity among the evaluated plots.